Global effects of the CSR-1 RNA interference pathway on the transcriptional landscape - Cecere, Germano; Hoersch, Sebastian; O'Keeffe, Sean; Sachidanandam, Ravi; Grishok, Alla (Nature structural & molecular biology, 2014)
RNAi pathways inhibit gene expression at the transcriptional and post-transcriptional level. Genome-wide analyses of nascent RNA transcripts in nematodes now suggest that the CSR-1 RNAi pathway helps maintain the directionality of active transcription and propagate the distinction between transcriptionally active and silent genomic regions. Argonaute proteins and their small RNA cofactors short interfering RNAs are known to inhibit gene expression at the transcriptional and post-transcriptional levels. In Caenorhabditis elegans , the Argonaute CSR-1 binds thousands of endogenous siRNAs (endo-siRNAs) that are antisense to germline transcripts. However, its role in gene expression regulation remains controversial. Here we used genome-wide profiling of nascent RNA transcripts and found that the CSR-1 RNA interference pathway promoted sense-oriented RNA polymerase II transcription. Moreover, a loss of CSR-1 function resulted in global increase in antisense transcription and ectopic transcription of silent chromatin domains, which led to reduced chromatin incorporation of centromere-specific histone H3. On the basis of these findings, we propose that the CSR-1 pathway helps maintain the directionality of active transcription, thereby propagating the distinction between transcriptionally active and silent genomic regions.